Beyond empathy training for practitioners: Cultivating empathic healthcare systems and leadership - Howick, J; de Zulueta, P; Gray, M (Wiley, 2024)
Empathic care benefits patients and practitioners, and empathy training for practitioners can enhance empathy. However, practitioners do not operate in a vacuum. For empathy to thrive, healthcare consultations must be situated in a nurturing milieu, guided by empathic, compassionate leaders. Empathy will be suppressed, or even reversed if practitioners are burned out and working in an unpleasant, under‐resourced environment with increasingly poorly served and dissatisfied patients. Efforts to enhance empathy must therefore go beyond training practitioners to address system‐level factors that foster empathy. These include patient education, cultivating empathic leadership, customer service training for reception staff, valuing cleaning and all ancillary staff, creating healing spaces, and using appropriate, efficiency saving technology to reduce the administrative burden on healthcare practitioners. We divide these elements into environmental factors, organisational factors, job factors, and individual characteristics.